Acute Hemorrhagic Edema of Infancy: A Case Series of Three Cases (Indian Journal of Case Reports, 2020)
Acute hemorrhagic edema of infancy (AHEI) is a poorly known benign vasculitis. With a rapid course, self-limited evolution, and without specific diagnostic tests, it is poorly diagnosed. It has differential diagnosis with Henoch–Schönlein’s purpura, multiform erythema, Kawasaki’s incomplete disease, or urticaria. We present a case series of three cases of children with a clinical diagnosis of AHEI, and in two of them, a biopsy was performed which confirmed the diagnosis. The three children have a maculopapular purpuric eruption, fever, and edema at the extremities. They were treated with symptomatic medications and showed improvement in a few days. AHEI is a rare vasculitis, sometimes underdiagnosed, due to the similarity with other differential diagnoses, much more prevalent. As it is not frequently described, and due to the exuberance of symptoms, it is a disease susceptible to diagnostic errors and iatrogenic treatments.